PENGARUH SISTEM PERPAJAKAN, DISKRIMINASI, TEKNOLOGI DAN INFORMASI PERPAJAKAN TERHADAP PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK: (Studi Pada Wajib Pajak Orang Pribadi di Universitas Majalengka) - Rizal Sukma Aliyudin; Eva Fauziah Ahmad; Nissa Nizhan (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2021)
This study aims to determine the effect of taxation systems, discrimination, technology and tax information on the perception of taxpayers at Majalengka University regarding tax evasion. The data used in this study are primary data. Primary data were obtained from questionnaires and measured using a Likert scale. The population used in this study is an individual taxpayer at Majalengka University. This sampling technique used saturated sampling with a sample of 280 respondents. The data analysis used descriptive analysis, verification analysis, classical assumption test, multiple linear regression analysis, determination coefficient analysis and hypothesis testing with the help of SPSS version 21. The results showed that: (1) the taxation system had no significant effect on taxpayers' perceptions of tax evasion; (2) discrimination has a significant effect on taxpayers' perceptions of tax evasion; (3) technology and tax information do not have a significant effect on taxpayers' perceptions of tax evasion.